Site-directed mutagenesis to determine the role of surface exposed lysine on the stability of staphylococcal lipase - Ahmad, Nurul Nadirah (2020)
Protein stability is governed mainly by the intrinsic characteristics of the protein such as the number and strength of intramolecular interactions and prevalence of specific amino acids in the sequence. Surface residue is one of the factors that defines protein stability, however little is known about their roles in relative to other factors. In this study, Staphylococcus epidermidis AT2 lipase which exhibits stability at low temperature and in the presence of organic solvents was subjected to surface lysine mutation to examine the effect of surface charged residue to the enzyme stability. As lysine denotes 7% out of the total amino acid composition, surface exposed and mutable lysine was identified to produce AT2 lipase mutants via in silico and analysed by Molecular Dynamics simulation. The mutant model structures were built using YASARA version 12.10.3 using S. hyicus lipase (PDB id: 2HIH) as template. The structures were validated by means of PROCHECK (Ramachandran plots), ERRAT2, Verify3D and QMEAN. The refined protein models were subjected to MD simulation in water environment using AMBER03 force field. Out of six mutant lipases, two mutants (K325G and K91A/K325G) showed improvement in structural stability by in silico analysis thus were selected for biochemical and biophysical characterizations. Both mutants exhibited a shift of 5°C in optimal temperature compared to the wild-type which optimum at 25°C. K325G and K91A/K325G showed optimum at 30°C and 20°C, respectively. K91A/K325G and the wild-type displayed similar pH profiles, pH 8, while mutant K325G exhibited slight changes of pH profile, pH 9. Meanwhile, no significant changes in substrate specificity were observed where the mutants showed similar preference towards long chain p-nitrophenyl esters. On the other hand, each mutant demonstrated slight alteration of the organic solvent stability profile upon mutation. A strong preference towards polar organic solvents and several other apolar solvents was observed in the mutants. Mutant K325G, generally, displayed enhancement and stability in DMSO, methanol, acetonitrile, ethanol, acetone, 1-propanol, diethyl ether and chloroform. While, K91A/K325G is stable in methanol, acetonitrile, ethanol and acetone. Analysis of melting temperature measured by circular dichroism showed that mutant K325G exhibited the highest melting temperature, 62.95°C which positively correlated with a 5°C shift in its optimal temperature compared to the wild-type, 53.25°C. In addition, K91A/K325G composed the highest percentage of α-helices (25.4%) meanwhile K325G with highest β-sheets; 52.9% compared to the wild-type. Further MD simulation studies were carried out in two solvents to investigate the activation and inactivation effect on the mutants and wild-type. In general, both mutants showed greater conformational stability compared to the wild-type in the presence of methanol. Methanol showed a profound local dynamic alteration to mutant K325G where the values of RMSF observed were between the range of 1 to 7 Å with the highest value at 7 Å. The apparent change was observed at the lid region (lid 1) suggesting a larger displacement of the lid. Such observation was not seen in the wild-type and the double mutant which could explain the enhancement of lipase activity in methanol where the large opening of the lid might increase the accessibility of substrate to the catalytic pocket. The inactivation effect of n-hexane however could not be concluded as there was no significant event observed throughout the trajectories. As conclusion, this study highlights the strategy of replacing surface lysine with smaller residue to observe the effect of lysine residue to properties of enzyme. This approach can be considered as one of the parameters in protein stability engineering.